Setting the Moment of Income from Advances as a Tool for Tax Strategy of Enterprises - Jarczok-Guzy, Magdalena (Journal of Finance and Financial Law, 2017)
This article shows the influence of application of general rules and new regulations on determining the inception of the income tax from received advance payments of corporate income tax and personal income tax on the liquidity of the company. Simplifying in the rules obliged since 2015 entitle taxpayers using cash registers to identify the moment of check in advance with the moment of revenue. The impact of described regulation on the formation of moment of income tax liability has been illustrated by a numerical example.